Urgensi Penguatan Ketentuan Hukum Perlindungan Konsumen Pasca Diterapkan Sistem Perdagangan Bebas di Indonesia - Anggono, Aris Bayu (Universitas Ekasakti, 2023)
Law Number 8 of 1999 Concerning Consumer Protection (UUPK) states that consumer protection is all efforts that guarantee legal certainty to provide protection to consumers. As consumers, the public is often in a weak position, one of the causes of this weakness is the weakening of power in regulating and supervising consumer rights. Currently, free trade supported by advances in communication technology has ecpanded the space for the flow of transactions of goods and/or services between countries, this condition, on the one hand, has benefits for consumers because all consumer needs can be met, as well as more freedom to choose various types of quality goods and services according to the wishes and abilities of consumers. However, on the other hand, such conditions can result in the consumer’s position being in a weak position and consumer protection rules that are no longer sufficient to keep up with the developments and sophistication of the times. Everything related to the purchase of goods/services regulates consumer rights. But in fact, currently consumer protection provisions are unable to act as a legal umbrella in the era of free trade with the existence of business actors who do not pay attention to consumer rights. Strengthening consumer protection in Indonesia after free trade is absolutely necessary to provide protection to the public and create a balance between business and consumers. Efforts to improve consumer protection by amending the UUPK, strenghthening consumer protection institutons, providing consumer education and a commitment to establising laws and regulations that protect consumers.